User Experience of a 3D Interactive Human Anatomy Learning Tool - Chaker, Rawad; Gallot, Mélanie; Binay, Marion; Hoyek, Nady (Educational Technology ＆ Society, 2021)
Embodiment is particularly relevant for learning anatomy as the knowledge to be acquired is related to the body itself. Several tools using three-dimensional (3D) anatomical structures and avatars (e.g. augmented reality; virtual reality; immersive anatomy; 3D animations) were developed to enrich students' experience by including gestures and body movements into learning anatomy. We developed a new interactive 3D tool that allows personal body experience and enhances spatial representation of musculoskeletal functional anatomy. Students can analyze and recreate a series of movements in real-time 3D interactive settings. This paper shows our research and development approach. Following the development of our anatomy tool, we conducted a pilot and one experiment. The pilot study aimed at evaluating users' experience (UX) of our first prototype. Experiment I aimed at evaluating the UX of the second version of the tool two times in a pretest-training-posttest design. Students' spatial and motor imagery abilities as well as anatomy examination results were also collected. Our results provided evidence of UX enhancement. Accordingly students appreciated mainly the tool's hedonic (enjoyment) qualities. Overall, significant interactions were observed between students' UX, anatomy scores and motor imagery abilities. Finally, students' mental rotation ability predicted the increase of anatomy score. Cognitive sub-processes underlying functional human anatomy learning as well as students' identification through the avatar are discussed.